Comparative Study: Analysis of the Implementation of Sustainable Distribution of Funds for Sharia Banks and Conventional Banks in Indonesia - nihayah, ana zahrotun; Rifqi, Lathif Hanafir (AL-ARBAH: Journal of Islamic Finance and Banking, 2023)
Purpose - This research aims to identify the application of sustainable finance in sharia banks and conventional banks and identify obstacles in the application of sustainable finance.Method - The method used in this research is qualitative with a descriptive design. The type of descriptive design method used is a comparative study.Result - The research results show that the implementation of sustainable finance as represented by the allocation of financing at conventional banks (BRI) reached 65.5%, higher than sharia banks (BSI) which only reached 26.95%. the establishment of rules and regulations that are not yet comprehensive in the financial sector, low financial inclusion, low sustainable finance literacy, lack of common perception in financial institutions, the difficulty of balancing economic, social and environmental aspects and low market potential in lending to environmentally sound companies.    Implication - This research was conducted to provide an explanation of the implementation of sustainable distribution of funds in Sharia banks and conventional banks and its challenges.  Originality - Several previous studies have discussed sustainable finance in banking. However, there are still few discussing the comparison of the implementation of sustainable finance and the risks involved.